Mothers participation in caring for hospitalized children with acute gastroenteritis: A quasi‐experimental study - Haniyeh Nankali; Fatemeh Cheraghi; Tayebeh Hasan Tehrani; Younes Mohammadi; Mahnaz Azadimoghtader (Wiley, 2023)
Abstract Aims To identify informational and practical deficits of mothers of hospitalized children with acute gastroenteritis and to determine the effect of intervention on enhancing mothers' participation in providing care. Design This study was a two‐group pre‐ and post‐test quasi‐experimental study. Methods Sample size was eighty mothers of hospitalized children younger than 5 years with acute gastroenteritis in each group using consecutive sampling method. Based on the needs assessment, the training and practical demonstration were performed individually in the intervention group. The control group received usual and standard care. The care practice of mothers were observed before and three times after the intervention at a 1‐day interval. The confidence level was 0.95. Results After intervention, there was a significant increase in the mothers' care practice in the intervention group and a significant difference between the two groups. The participatory care approach could enhance mothers' practice in providing care to the hospitalized children with AGE.